How privacy may be protected in optional randomized response surveys - Sanghamitra Pal; Arijit Chaudhuri; Dipika Patra (Statistics in Transition New Series, 2020)
There are materials in literature about how privacy on stigmatizing features like alcoholism, history of tax-evasion, or testing positive in AIDS-related testing may be partially protected by a proper application of randomized response techniques (RRT). The paper demonstrates what amendments are necessary for this approach while applying optional RRTs covering qualitative characteristics, permitting a sampled respondent either to directly reveal sensitive data or choose a randomized response respectively with complementary probabilities. Only a few standard RRTs are illustrated in the text.
Keywords: 519; protection of privacy; randomized response; sensitive issues; Warner and other techniques